1996
DOI: 10.1007/bf01875593
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal injection of sulfur amino acids enhance the hepatic cysteine dioxygenase activity in rainbow trout (Oncorhynchus mykiss)

Abstract: As part of the investigation into cysteine metabolism in fish, sulfur amino acids and their derivatives were injected intraperitoneally to fingerling rainbow trout (Oncorhynchus mykiss) to examine how the doses of these compounds affect the hepatic cysteine dioxygenase [EC 1.12.11.20] in this species. A dose of 0.25 mmol L-cysteine per 100 g body weight induced the enzyme activity as much as 2.5 times that of the control fish within 4h after the injection. The activity increased proportionally to the increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Likewise, low hypotaurine production observed in other teleost species suggest that dietary taurine is required by the animal, which was indeed later confirmed for Japanese flounder (Kim et al, 2005a), red sea bream (Matsunari et al, 2008b), and yellowtail (Takagi et al, 2008). Intraperitoneal injection of cysteine elicited an increase in CDO activity (Yokoyama and Nakazoe, 1996), while the resulting cysteine sulfinic acid was subsequently equally split between hypotaurine and sulfate products (Yokoyama et al, 1997), suggesting that taurine is produced along pathway I in rainbow trout. However, hypotaurine production was extremely low in common carp (Yokoyama et al, 2001), although this…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Likewise, low hypotaurine production observed in other teleost species suggest that dietary taurine is required by the animal, which was indeed later confirmed for Japanese flounder (Kim et al, 2005a), red sea bream (Matsunari et al, 2008b), and yellowtail (Takagi et al, 2008). Intraperitoneal injection of cysteine elicited an increase in CDO activity (Yokoyama and Nakazoe, 1996), while the resulting cysteine sulfinic acid was subsequently equally split between hypotaurine and sulfate products (Yokoyama et al, 1997), suggesting that taurine is produced along pathway I in rainbow trout. However, hypotaurine production was extremely low in common carp (Yokoyama et al, 2001), although this…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Historically, taurine has not been considered as an essential nutrient for fish (Robinson et al . ; Borlongan & Coloso ; Yokoyama & Nakazoe ; Akiyama et al . ).…”
Section: Taurine Biosynthesis and Metabolismmentioning
confidence: 99%
“…Historically, taurine has not been considered as an essential nutrient for fish (Robinson et al 1978;Borlongan & Coloso 1993;Yokoyama & Nakazoe 1996;Akiyama et al 1997). Just recently, studies have indicated that taurine synthesis widely differs between fish species, depending on fish species and size, feeding habits and cysteinesulphinate decarboxylase (CSD) activity.…”
Section: Taurine Biosynthesis and Metabolismmentioning
confidence: 99%
“…13.11.20) increases and hepatic ␥-glutamylcysteine synthetase (GCS; EC 6.3.2.2) decreases when animals are fed diets high in protein or sulfur amino acids [12][13][14]. Marked changes in CDO and GCS levels occur when dietary protein is increased from below-requirement levels to above-requirement levels [15][16][17].…”
Section: Introductionmentioning
confidence: 99%